2022
DOI: 10.3758/s13423-022-02082-4
|View full text |Cite
|
Sign up to set email alerts
|

Long-term memory interference is resolved via repulsion and precision along diagnostic memory dimensions

Abstract: When memories share similar features, this can lead to interference, and ultimately forgetting. With experience, however, interference can be resolved. This raises the important question of how memories change, with experience, to minimize interference. Intuitively, interference might be minimized by increasing the precision and accuracy of memories. However, recent evidence suggests a potentially adaptive role for memory distortions. Namely, similarity can trigger exaggerations of subtle differences between m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 47 publications
2
3
1
Order By: Relevance
“…We extend this literature by showing how different kinds of features exhibit varying susceptibility to memory distortions depending on their role in a category. Although there has been limited prior work examining feature-level memory distortions in category learning, one study found that participants misremembered pairs of faces as less similar to one another (repulsion) along the facial feature dimension most diagnostic for differentiating the two faces (Drascher & Kuhl, 2022). This finding is consonant with the findings we report here for unique features, where information that is diagnostic of an item showed reduced attraction (though not repulsion).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…We extend this literature by showing how different kinds of features exhibit varying susceptibility to memory distortions depending on their role in a category. Although there has been limited prior work examining feature-level memory distortions in category learning, one study found that participants misremembered pairs of faces as less similar to one another (repulsion) along the facial feature dimension most diagnostic for differentiating the two faces (Drascher & Kuhl, 2022). This finding is consonant with the findings we report here for unique features, where information that is diagnostic of an item showed reduced attraction (though not repulsion).…”
Section: Discussionsupporting
confidence: 87%
“…Related distortions in perception have also been long-documented via the phenomenon of categorical perception (Dubova & Goldstone, 2021;Folstein et al, 2015;Goldstone, 1994), where features near a category boundary are perceived as more distinct. Our work differs from this literature, as well as Drascher & Kuhl (2022), in showing how features relating to the internal structure of a category, as opposed to discrimination boundaries, are distorted, and demonstrating effects in an attribute (color) that does not itself carry information about feature roles (whether a feature is unique or shared) in the category.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…This is precisely what we found in our analyses of lure representationstesting exerted the biggest impact on moderatestrength lures, which were significantly repelled away from cue words, relative to weak/non-lure pairings. This effect is not only consistent with the predictions of NMPH, but also with an emerging body of work showing that competition adaptively distorts and repels overlapping episodic representations so they become less similar 46,64,65 .…”
Section: Discussionsupporting
confidence: 85%
“…Prior experimental work has demonstrated that representations of highly similar episodic memories are both reactivated during memory retrieval 68,69 . Competition adaptively distorts overlapping episodic representations so they become less similar; the amount that overlapping representations are repelled is predictive of subsequent memory 44,70,71 . We showed that potential semantic lures are pushed away from the cue in representational space only for semantically related pairs, suggesting that preexisting connections between cue and target can be used as retrieval cues, but that additional shared concepts must be repelled for the connections to be used successfully.…”
Section: Discussionmentioning
confidence: 99%